(untitled) (Journal of Enam Medical College, 2024)
Background: Online learning is a form of education that takes place over the Internet. With the advancement of information and communication technologies, the acceptance of online education is increasing. It is an alternative to traditional classroom learning and involves using primarily the internet and one or more other technologies. Objective: To identify the advantages and disadvantages of online learning from the student’s perspective. Materials and Methods: Data were collected from 256 MBBS students of Enam Medical College with a predesigned questionnaire by purposive sampling to assess the student’s perception towards the online teaching-learning modalities, its advantages, limitations and recommendations how the online teaching and learning process can be made more effective. Results: The findings of the study revealed that most of the students are self-educated and lack of institutional knowledge regarding ICT tools and online learning process. The study result showed several advantages including; it is flexible regarding the time and place, sharing of information is easy and cost effective. Whereas, lack of face-to-face interaction, less effective in practice-based learning, disturbance of physical health, lack in student feedback, reliable internet connection, lack in computer skills and limited infrastructure at work place are identified as challenges. The students have also given their opinion regarding the possible steps and strategies to improve the online learning more effective. Conclusion: As with most teaching methods, online learning also has its own set of positives and negatives. Several initiatives like; more communication between students and teachers, use of more suitable technology, supporting the struggling students and creating a sense of comfort can make it more effective. J Enam Med Col 2022; 12(1): 17−23